Study of midterm outcome of spinal fusion in low grade spondylolisthesis - Tuse, Sushant Sopan; Matin, Aamir; Kaware, Rohit Suresh; Dhamdhare, Saurabh Sunil; Gursale, Amey; Patil, Nilesh; Mesare, Vaibhav Ukarda; Borse, Amey Mahesh (International Journal of Research in Orthopaedics, 2022)
Background: The objective of our study is to measure clinical and radiological outcome of spinal fusion in low grade spondylolisthesis at minimum 5 years following surgery. Methods: Monocenteric prospective observational study was conducted to assess the mid-term outcome of spinal fusion in low grade spondylolisthesis with minimum 5 years following surgery in patients who underwent surgery from 2010 to 2015 in department of orthopaedics of Seth Nandlal Dhoot hospital, Aurangabad. Out of total 51 participants, there were 24 males and 27 females with mean age of 55.90 years of study participants. The patients were evaluated radiologically with AP and lateral X-rays views and dynamic flexion and extension views were taken and was evaluated with Lenke method and clinically with the visual analog scale (VAS) for back and leg pain, the Oswestry disability index (ODI), and the physical component (Physical functioning) of SF-36 health survey at minimum 5 years following surgery. Results: In our study we observed high spinal fusion rate of 96.1% and satisfactory improvement in clinical outcome at minimum 5 years following surgery in 51 study participants who underwent spinal fusion for low grade spondylolisthesis. Conclusions: The spinal fusion in low grade spondylolisthesis is a safe, simple and less morbid approach with low complication rate. We observed 96.1% of spinal fusion rate and highly significant decrease in post-operative mean ODI score, mean SF-36 physical component and mean VAS score with 78.4% patient did not develop any complications. Spinal fusion provides better functional outcome by providing pain relief and improving the quality of life in the patients. Spinal fusion restores the normal sagittal balance of spine and maintains the disc space height and also provides better fusion rates.